COVID-19 and Women in the Labour Market in the Federation of Bosnia and Herzegovina - Ranko Markuš; Bahrija Umihanić; Ljiljan Veselinović (ICEI 2021, Economic Response and Crisis Recovery Caused by the Covid-19 Pandemic, Conference proceedings: 7th Scientific Conference with International Participation, Tuzla, December 2th-4th, 2021, 2021)
In this paper, authors present the results of a research study on the representation of women in the labour market within fifteen activities in the Federation of Bosnia and Herzegovina. In four of the fifteen industries, women are more represented than men. Authors investigated the resilience of companies to the challenges of the COVID-19 pandemic using a large sample of 1,232 companies operating in the Federation of BiH and focusing on determining the success of companies measured by financial performance and reducing the number of women and men employed in companies. The results of the research indicate that 50.1% of companies in which women are more represented reported a decline in financial performance, compared to 38.6% of companies in which men are more represented, and that 4.1% of women lost their jobs compared to 2.6% of men. The results of this study could be valuable in promoting the need to establish various measures to combat the low participation of women in the labour market.
Keywords: J21; 330; COVID-19; women; labour market